Impact of Natalizumab Treatment on Fatigue, Mood, and Aspects of Cognition in Relapsing–Remitting Multiple Sclerosis - Kunkel, Annett; Fischer, Martin; Faiss, Judith; Dähne, Doreen; Köhler, Wolfgang; Faiss, Jürgen H. (Frontiers in Neurology, 2015)
Background/Objective Fatigue, cognitive and affective disorders are relevant symptoms in Multiple Sclerosis (MS). The treatment with Natalizumab has a positive effect on physical disabilities in patients with RRMS. Some studies describe improvements in cognition and fatigue over one year of treatment. Only little is known about longer treatment effects especially on fatigue, but also on cognition and mood. Therefore the present retrospective open label observational study investigates the effect of Natalizumab on fatigue, attention and depression over a treatment period of two years. Methods 51 RRMS patients that were treated with Natalizumab (male = 11, female = 40; mean age: 33,9+9,1 years) were included. The neuropsychological assessment consisted of different tests of attention (TAP: alertness, divided attention, flexibility, SDMT, PASAT), fatigue (WEIMUS, FSMC) and depression (CES-D). The assessments occurred immediately before the first administration of Natalizumab, after one and two years of treatment. Results Significant improvements were found in aspects of attention and depression from baseline to follow-up 1 (alertness: reaction time (RT) cued, p < 0.05; divided attention: visual RT, p < 0.05; SDMT: p = 0.05; CES-D: p < 0.05) and from baseline to follow-up 2 (divided attention: visual RT: p < 0.001; errors: p < 0.01, omissions: p < 0.05; flexibility: RT, p < 0.05; SDMT: p < 0.01; CES-D: p < 0.05). No significant changes were detected in fatigue probably because of the small sample size especially in the second year of treatment (WEIMUS: N = 16, FSMC: N = 8). Conclusion The results show a positive effect of Natalizumab on attention in patients with RRMS and for the first time also in depression after two years of observation and support the efficacy of the treatment over two years. More research is needed for fatigue.